Lesson of the month 1: Prolonged QT syndrome due to donepezil: a reversible cause of falls? - Jackson, Emily G (Clin Med (Lond), 2019)
Prolonged QT syndrome precipitates cardiac arrhythmias such as torsades de pointes (TdP) resulting in cardiogenic syncope or sudden death. We report a case of prolonged QT syndrome caused by donepezil which resulted in a fall and hip fracture. In this case female sex, advanced age and diuretic use may have increased the risk of recurrent syncope and potential underlying TdP. Cessation of donepezil resulted in normalisation of the QT interval. This case highlights a lesser known side effect of this dementia drug. It also reminds us of the importance of taking a thorough drug history while considering potential drug toxicity/interactions as part of the comprehensive geriatric assessment.